Morphologic Features of Extrahepatic Manifestations of Hepatitis C Virus Infection - Huaibin M. Ko; Juan C. Hernandez-Prera; Hongfa Zhu; Steven H. Dikman; Harleen K. Sidhu; Stephen C. Ward; Swan N. Thung (Clinical and Developmental Immunology)
Cirrhosis and hepatocellular carcinoma are the prototypic complications of chronic hepatitis C virus infection in the liver. However, hepatitis C virus also affects a variety of other organs that may lead to significant morbidity and mortality. Extrahepatic manifestations of hepatitis C infection include a multitude of disease processes affecting the small vessels, skin, kidneys, salivary gland, eyes, thyroid, and immunologic system. The majority of these conditions are thought to be immune mediated. The most documented of these entities is mixed cryoglobulinemia. Morphologically, immune complex depositions can be identified in small vessels and glomerular capillary walls, leading to leukoclastic vasculitis in the skin and membranoproliferative glomerulonephritis in the kidney. Other HCV-associated entities include porphyria cutanea tarda, lichen planus, necrolytic acral erythema, membranous glomerulonephritis, diabetic nephropathy, B-cell non-Hodgkin lymphomas, insulin resistance, sialadenitis, sicca syndrome, and autoimmune thyroiditis. This paper highlights the histomorphologic features of these processes, which are typically characterized by chronic inflammation, immune complex deposition, and immunoproliferative disease in the affected organ.